Associations Between Pressure–Pain Threshold, Symptoms, and Radiographic Knee and Hip Osteoarthritis1. Issue 10 (October 2014) - Goode, Adam P.; Shi, Xiaoyan A.; Gracely, Richard H.; Renner, Jordan B.; Jordan, Joanne M.
<x xml:space="preserve">Abstract</x> Objective To determine the association between generalized evoked pressure pain sensitivity with distal pressure–pain threshold (PPT) and the presence, severity, or number of involved knee/hip joints with radiographic osteoarthritis (rOA) or related symptoms. Methods Data for these cross‐sectional analyses come from the second followup (2008–11) of the Johnston County Osteoarthritis Project (n = 1, 602). PPT measurements were averaged over 2 trials from both the left and right trapezius. Outcomes of radiographic knee and hip OA were both defined by a Kellgren/Lawrence score of 2–4 and site‐specific symptoms were ascertained at clinical interview. Associations were determined with multiple logistic regression models and two‐way interactions were tested at P < 0.05. Results The sample was 67.2% women and 31.0% African American. Participants' mean ± SD age was 67.9 ± 9.0 years, mean ± SD body mass index was 31.5 ± 7.1 kg/m2, mean ± SD Center for Epidemiologic Studies Depression Scale score was 6.5 ± 7.4, and mean ± SD total PPT was 3.6 ± 0.7 kg. Significant associations were found between PPT and self‐reported knee/hip symptoms. No significant associations were found between PPT and presence, severity, or number of joints with knee and hip rOA without accompanying symptoms. No significant interactions were found with demographic or clinical characteristics. Conclusion PPT was significantly associated with self‐reported single and multijoint symptoms. In contrast, after adjustment, PPT measured at the trapezius was not associated with asymptomatic knee or hip rOA. As such, PPT may prove to be a useful indicator of rOA pain processing and of why individuals respond favorably and others do not to treatments targeting rOA.